Identification and Climatology of Alpine Pumping from a Regional Climate Simulation - Graf, Maximilian; Kossmann, Meinolf; Trusilova, Kristina; Mühlbacher, Gudrun (Frontiers in Earth Science, 2016)
The thermally driven circulation between the European Alps and the alpine foreland - named Alpine pumping – occurs regularly under clear and calm weather conditions. While previous studies focused on the impact of Alpine pumping on moist convection and transport of air pollutants, this study was motivated by its ventilation effect for Munich, located about 50 km north of the Alps in undulating and only slightly inclined terrain, where local thermal circulations are weak. Hourly data from a reanalysis driven regional climate simulation with COSMO-CLM model for the period 1989 to 2008 were analysed to identify days with Alpine pumping and to determine the mean diurnal characteristics of this regional thermal circulation. Four literature derived combinations of meteorological criteria were tested to identify days favorable for Alpine pumping from COSMO-CLM results. The first criterion selects days with a daily sum of solar radiation ≥20 MJ/m2 and has been used in an earlier observational study. On average 60 d/y are fulfilling the criterion in the model simulation, which compares well to the 67 d/y determined from observations. The other three criteria combinations consider a maximum wind velocity at 850 hPa, a maximum daily precipitation sum, and/or a maximum mean cloud cover. The mean annual number of selected days is lower for these criteria combinations and ranges between 20 and 52. Diurnal wind reversals occur on 77 to 81% of the selected days, depending on the criteria combination The daily solar radiation sum of 20 MJ/m2 is only exceeded during April to September, while days satisfying the criteria combinations without the radiation threshold occur all year round. In agreement with observations, the simulated regional thermally driven wind field extends up to ~100 km north of the Alps with average near-surface wind speeds of 0.5-1.5 m/s in the Munich area. With increasing distance from the Alps, the diurnal cycle of Alpine pumping is delayed by up to 3 hours. The simulated mean depth of the daytime inflow layer ranges between 500 m and 1500 m, whereas the depth of the nocturnal outflow layer typically reaches up to a few hundred meters.